“Eu tenho pra vender, quem quer comprar?”: análise socioeconômica sobre a atuação das quitandeiras em Belém do Pará na transição do século XIX para o século XX - SILVA, Júlia Brenda Palheta da (2024)
The current work aims to carry out a socioeconomic analysis of women greengrocers in the city of Belém between the 19th and 20th centuries. In order to understand the active participation of these women in historiography, in this research, they will be thought of through sources considered official, aiming to overcome the colonial and dominion stigmas imposed on these individuals and their bodies. Through this perspective, it was possible to perceive the importance of understanding them through their own voices, in which they appear not only as dominated subjects, but important women for the dynamization of part of the economy of Pará, but also for the construction of society. Through this object of study, it will be possible to perceive that, despite the attempt at silencing, these women built the scene of the streets and were fundamental, since through sales, they fed a large part of the population and for this reason they did not go unnoticed in the streets. sources that aimed to marginalize them.